Enhanced-Sampling Simulations for the Estimation of Ligand Binding Kinetics: Current Status and Perspective - Ahmad, Katya; Rizzi, Andrea; Capelli, Riccardo; Mandelli, Davide; Lyu, Wenping; Carloni, Paolo (Frontiers in Molecular Biosciences, 2022)
The dissociation rate (koff) associated with ligand unbinding events is a parameter of fundamental importance in drug design. Here we review recent major advancements in molecular simulation methodologies for the prediction of koff. Next, we discuss the impact of the potential energy function models on the accuracy of calculated koff values. Finally, we provide a perspective from high-performance computing and machine learning which might help improve such predictions.